Rhodaelectrocatalysis for Annulative C−H Activation: Polycyclic Aromatic Hydrocarbons through Versatile Double Electrocatalysis. (1st April 2019) - Kong, Wei‐Jun; Finger, Lars H.; Oliveira, João C. A.; Ackermann, Lutz
Abstract: Rapid access to structurally diversified polycyclic aromatic hydrocarbons (PAHs) in a controlled manner is of key significance in materials sciences. Herein, we describe a strategy featuring two distinct electrocatalytic C−H transformations for the synthesis of novel nonplanar PAHs. The combination of rhodaelectrooxidative C−H activation/[2+2+2] alkyne annulation of easily accessible boronic acids with electrocatalytic cyclodehydrogenation provided modular access to diversely substituted PAHs with electricity as a sustainable oxidant. The unique molecular topology as well as the photophysical and electronic properties of the thus obtained PAHs were fully analyzed. The unique power of this metallaelectrocatalysis method was demonstrated by the chemoselective assembly of synthetically useful iodo‐substituted PAHs. Abstract : Da ist Saft drauf ! Die Kombination einer rhodaelektrooxidativen C‐H‐Aktivierung/[2+2+2]‐Alkinanellierung von leicht zugänglichen Boronsäuren mit elektrokatalytischer Cyclodehydrierung bietet einen modularen Zugang zu unterschiedlich substituierten polycyclischen aromatischen Kohlenwasserstoffen unter Einsatz von Elektrizität als nachhaltigem Oxidationsmittel.